2018
DOI: 10.1002/hpm.2586
|View full text |Cite
|
Sign up to set email alerts
|

Rwandan stakeholder perspectives of integrated family planning and HIV services

Abstract: SummaryThe purpose of this qualitative study was to understand the knowledge, attitudes, and practices among key Rwandan policymakers and stakeholders related to family planning (FP) and integrated HIV/FP services. Motivational in-depth interview format and content was developed after an extensive policy review. A convenience sample of 10 high-level HIV and FP Rwandan policymakers and stakeholders completed the interview. Stakeholders demonstrated strong foundational knowledge of HIV and FP. Given the choice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similar to other African countries [50][51][52][53], there is consensus among stakeholders in Rwanda that HIV and family planning (FP) services should be integrated [54]. The Government of Rwanda strongly supports access to the full range of contraceptive options [55] and provides free therapeutic antiretrovirals (ARV) and PMTCT for HIV [56].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other African countries [50][51][52][53], there is consensus among stakeholders in Rwanda that HIV and family planning (FP) services should be integrated [54]. The Government of Rwanda strongly supports access to the full range of contraceptive options [55] and provides free therapeutic antiretrovirals (ARV) and PMTCT for HIV [56].…”
Section: Introductionmentioning
confidence: 99%
“…25 Similar findings have also been reported in a multicountry analysis of Demographic and Health Survey data among men from Chad, Ghana, Malawi, Nigeria, Tanzania, Uganda, Zambia, and Zimbabwe. 26 This may be attributed to the mature couple testing strategies 27 and community-based interventions that promote partners testing through secondary distribution of HIV self-test kits. 28,29 Further, HIV status disclosure strategies may also account for the improved testing rates among married men compared.…”
Section: Discussionmentioning
confidence: 99%
“…However, current policies have not yet resulted in integration nor nationwide promotion of LARC methods [ 40 , 41 ]. Data from a recent qualitative study of interviews with key Rwandan policymakers and stakeholders indicated that the best way to integrate HIV and family planning services was through development of integrated training materials, data collection tools, and advocacy and policy guidance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%